Hungary : Measuring Inclusive Growth for Enhanced Development Impact - World Bank (Washington, DC, 2016)
The objective of this paper is to develop a way to monitor and track progress on social inclusion of vulnerable groups in Hungary, particularly among marginalized Roma communities. This approach will enable stakeholders to track the status of social inclusion at the sub regional level, and can serve as a feedback mechanism on whether projects cosponsored by the European structural and investment funds (ESIF) are sufficiently targeted to disadvantaged areas. The paper builds on various Hungarian attempts to draft indicator sets to find and subsequently gear European Union (EU) - funded projects toward areas with the poorest social inclusion outcomes. This report takes stock of different exercises undertaken with Hungarian data to map, target, track, and monitor some aspects of social exclusion at different levels of disaggregation. The authors present four such attempts to: (i) map marginalized communities; (ii) target the most disadvantaged micro regions; (iii) track selected social inclusion goals; and (iv) model at risk of poverty (AROP) rates at the micro regional level. The report examines what has been done in international practice in terms of selecting and collecting indicators that measure social inclusion. The report describes the method and process of indicator selection for Hungary. The concluding section summarizes the dilemmas associated with dynamically measuring social change in the Hungarian context, and presents development project parameters that should be continuously followed in order to enable tracking and (limited) monitoring.